Existence results for a family of equations of fractional resolvent - Rabha W. Ibrahim,; Sayyedah A. Qasem,; Zailan Siri, (Universiti Kebangsaan Malaysia, 2015)
This study deals with the presence and distinction of bounded m-solutions (type mild) for a family of generalized integral and differential equations of spot order with fractional resolvent and indefinite delay.